Spectrum measurement of variable irradiance controlled LED-based solar simulator - (:unkn) unknown (International Journal of Renewable Energy Research, 2020)
Efficiency of photovoltaic devices are based on testing all equipment and systems used to produce devices in a healthy way, from electrical and optical points of view. Considering that photovoltaic devices which enable the generation of electric energy from solar energy as a renewable energy source are widely used solar simulators should be utilized to provide actual daylight spectrum distributions. The most considerable component of solar simulators in photovoltaic device research is the light sources they use. Due to their advantages over conventional light sources, such as compactness, low power consumption, and low cost, research and studies on solar simulators use LEDs took place as their illumination source. In this study, it is aimed to produce a low-cost Class A solar simulator with using six different type power LEDs, as specified in the IEC 60904-9 and ASTM E927-05 standards. At the end of the study with 24 power LEDs with six different wavelengths, the spectral match which is one of the three performance criteria of the solar simulator was obtained as Class A. This study shows that LED-based solar simulators provide great savings in terms of energy consumption as well as a huge advantage in cost, compared to the widely used xenon arc lamp solar simulators. © 2020, International Journal of Renewable Energy Research.
Keywords: Light emitting diodes; Photovoltaic effects; Simulation; Solar energy; Spectroradiometers